Lipophilicity trends upon fluorination of isopropyl, cyclopropyl and 3-oxetanyl groups - Jeffries, Benjamin; Wang, Zhong; Troup, Robert I.; Goupille, Anaïs; Le Questel, Jean-Yves; Fallan, Charlene; Scott, James S.; Chiarparin, Elisabetta; Graton, Jérôme; Linclau, Bruno (Beilstein Journal of Organic Chemistry, 2020)
A systematic comparison of lipophilicity modulations upon fluorination of isopropyl, cyclopropyl and 3-oxetanyl substituents, at a single carbon atom, is provided using directly comparable, and easily accessible model compounds. In addition, comparison with relevant linear chain derivatives is provided, as well as lipophilicity changes occurring upon chain extension of acyclic precursors to give cyclopropyl containing compounds. For the compounds investigated, fluorination of the isopropyl substituent led to larger lipophilicity modulation compared to fluorination of the cyclopropyl substituent.
Keywords: aliphatic fluorination; cyclopropane; isopropyl; isostere; lipophilicity; oxetane

(untitled) - Persch, E.; Dumele, O.; Diederich, F. (Angew. Chem., Int. Ed., 2015)

(untitled) - Mecozzi, S.; Rebek, J., Jr (Chem. – Eur. J., 1998)

(untitled) - Bissantz, C.; Kuhn, B.; Stahl, M. (J. Med. Chem., 2010)

(untitled) - Zauhar, R. J.; Moyna, G.; Tian, L.; Li, Z.; Welsh, W. J. (J. Med. Chem., 2003)

(untitled) - Kumar, A.; Zhang, K. Y. J. (Front. Chem. (Lausanne, Switz.), 2018)

(untitled) - Smart, B. E. (J. Fluorine Chem., 2001)

(untitled) - Schönherr, H.; Cernak, T. (Angew. Chem., Int. Ed., 2013)

(untitled) - Kuntz, K. W.; Campbell, J. E.; Keilhack, H.; Pollock, R. M.; Knutson, S. K.; Porter-Scott, M.; Richon, V. M.; Sneeringer, C. J.; Wigle, T. J.; Allain, C. J.; Majer, C. R.; Moyer, M. P.; et al. (J. Med. Chem., 2016)

(untitled) - Barreiro, E. J.; Kümmerle, A. E.; Fraga, C. A. M. (Chem. Rev., 2011)

(untitled) - Talele, T. T. (J. Med. Chem., 2018)

(untitled) - Talele, T. T. (J. Med. Chem., 2016)

(untitled) - Novakov, I. A.; Babushkin, A. S.; Yablokov, A. S.; Nawrozkĳ, M. B.; Vostrikova, O. V.; Shejkin, D. S.; Mkrtchyan, A. S.; Balakin, K. V. (Russ. Chem. Bull., 2018)

(untitled) - Hansch, C.; Leo, A.; Unger, S. H.; Kim, K. H.; Nikaitani, D.; Lien, E. J. (J. Med. Chem., 1973)

(untitled) - Skagerberg, B.; Bonelli, D.; Clementi, S.; Cruciani, G.; Ebert, C. (Quant. Struct.-Act. Relat., 1989)

(untitled) - Letavic, M. A.; Aluisio, L.; Apodaca, R.; Bajpai, M.; Barbier, A. J.; Bonneville, A.; Bonaventure, P.; Carruthers, N. I.; Dugovic, C.; Fraser, I. C.; Kramer, M. L.; Lord, B.; et al. (ACS Med. Chem. Lett., 2015)

(untitled) - Wuitschik, G.; Carreira, E. M.; Wagner, B.; Fischer, H.; Parrilla, I.; Schuler, F.; Rogers-Evans, M.; Müller, K. (J. Med. Chem., 2010)

(untitled) - Wuitschik, G.; Rogers-Evans, M.; Müller, K.; Fischer, H.; Wagner, B.; Schuler, F.; Polonchuk, L.; Carreira, E. M. (Angew. Chem., Int. Ed., 2006)

(untitled) - Bull, J. A.; Croft, R. A.; Davis, O. A.; Doran, R.; Morgan, K. F. (Chem. Rev., 2016)

(untitled) - Böhm, H.-J.; Banner, D.; Bendels, S.; Kansy, M.; Kuhn, B.; Müller, K.; Obst-Sander, U.; Stahl, M. (ChemBioChem, 2004)

(untitled) - Huchet, Q. A.; Kuhn, B.; Wagner, B.; Fischer, H.; Kansy, M.; Zimmerli, D.; Carreira, E. M.; Müller, K. (J. Fluorine Chem., 2013)

Fluorine in Life Sciences: Pharmaceuticals, Medicinal Diagnostics, and Agrochemicals - Müller, K. (Fluorination patterns in small alkyl groups: their impact on properties relevant to drug discovery, 2018)

(untitled) - Linclau, B.; Wang, Z.; Compain, G.; Paumelle, V.; Fontenelle, C. Q.; Wells, N.; Weymouth-Wilson, A. (Angew. Chem., Int. Ed., 2016)

(untitled) - Panchaud, P.; Surivet, J.-P.; Diethelm, S.; Blumstein, A.-C.; Gauvin, J.-C.; Jacob, L.; Masse, F.; Mathieu, G.; Mirre, A.; Schmitt, C.; Enderlin-Paput, M.; Lange, R.; et al. (J. Med. Chem., 2020)

(untitled) - Nakahara, K.; Fuchino, K.; Komano, K.; Asada, N.; Tadano, G.; Hasegawa, T.; Yamamoto, T.; Sako, Y.; Ogawa, M.; Unemura, C.; Hosono, M.; Ito, H.; et al. (J. Med. Chem., 2018)

(untitled) - Fang, Z.; Cordes, D. B.; Slawin, A. M. Z.; O'Hagan, D. (Chem. Commun., 2019)

(untitled) - Thomson, C. J.; Zhang, Q.; Al-Maharik, N.; Bühl, M.; Cordes, D. B.; Slawin, A. M. Z.; O’Hagan, D. (Chem. Commun., 2018)

(untitled) - Wang, Z.; Jeffries, B. F.; Felstead, H. R.; Wells, N. J.; Chiarparin, E.; Linclau, B. (J. Visualized Exp., 2019)

(untitled) - Jeffries, B.; Wang, Z.; Felstead, H. R.; Le Questel, J.-Y.; Scott, J. S.; Chiarparin, E.; Graton, J.; Linclau, B. (J. Med. Chem., 2020)

(untitled) - Siebum, A. H. G.; Woo, W. S.; Lugtenburg, J. (Eur. J. Org. Chem., 2003)

(untitled) - Scott, J. S.; Bailey, A.; Buttar, D.; Carbajo, R. J.; Curwen, J.; Davey, P. R. J.; Davies, R. D. M.; Degorce, S. L.; Donald, C.; Gangl, E.; Greenwood, R.; Groombridge, S. D.; et al. (J. Med. Chem., 2019)

(untitled) - Zafrani, Y.; Sod-Moriah, G.; Yeffet, D.; Berliner, A.; Amir, D.; Marciano, D.; Elias, S.; Katalan, S.; Ashkenazi, N.; Madmon, M.; Gershonov, E.; Saphier, S. (J. Med. Chem., 2019)

(untitled) - Kubyshkin, V.; Budisa, N. (Beilstein J. Org. Chem., 2017)

The Practice of Medicinal Chemistry - Bazzini, P.; Wermuth, C. G. (Substituents and Functions: Qualitative and Quantitative Aspects of Structure–Activity Relationships, 2008)

(untitled) - Huchet, Q. A.; Kuhn, B.; Wagner, B.; Kratochwil, N. A.; Fischer, H.; Kansy, M.; Zimmerli, D.; Carreira, E. M.; Müller, K. (J. Med. Chem., 2015)

(untitled) - Erdeljac, N.; Kehr, G.; Ahlqvist, M.; Knerr, L.; Gilmour, R. (Chem. Commun., 2018)

(untitled) - Kundi, V.; Ho, J. (J. Phys. Chem. B, 2019)

(untitled) - Michalík, M.; Lukeš, V. (Acta Chim. Slovaca, 2016)